Influence of game-related statistical elements on final result at FIBA Eurobasket women 2017 - Simovic, S.; Komic, J.; Guzina, B.; Pajic, Z.; Vojvodic, M. (Facta Universitatis: Series Physical Education and Sport, 2018)
The research papers investigating the game-related parameters and phenomena of women's basketball matches are relatively smaller in size and number than the similar ones treating the same issues in men`s basketball - there has been some changes in that respect in recent years though. This paper`s sample of entity consisted of 40 games and thirteen variables of standard efficiency recorded at FIBA EuroBasket Women 2017. The research had two basic models of regressions formed, i.e. the absolute and the relative one, each of which had total numbers scored as the dependent variable, and was performed by means of regression and correlation analysis - stepwise regression, as a gradual method of fitting regression models in order to define predictive variables. The obtained regression models and partial correlation indicate that the winning or losing performance was heavily influenced by both field goal efficiency and defensive rebounding, all of which has been corroborated in many other similar pieces of research. Also, the variables as turnovers and personal fouls were extracted as significant in terms of differentiation between the winning and losing team. When we take a closer look and see the observed parameters from the point of view of either First or Final rounds of the competition - since these rounds were played in different formats - it is noticeable that it is becoming more and more evident, of course besides the shot efficiency, the efficiency of free throws and the quality of defense.